Polychromatic Light Exposure as a Therapeutic in the Treatment and Management of Parkinson's Disease: A Controlled Exploratory Trial - Willis, Gregory L.; Boda, Jamilee; Freelance, Christopher B. (Frontiers in Neurology, 2018)
Parkinson’s disease (PD) is a disorder characterised by loss of dopamine (DA) in the nigro-striatal dopamine (NSD) system with the primary symptoms of bradykinaesia, rigidity, tremor and altered gate. Secondary symptoms including depression, insomnia, involuntary movement and psychiatric side effects are also commonly observed. While the treatment focus for the past 50 years has been aimed at replacing deficient DA, to relieve the primary symptoms, more recent studies have suggested that the circadian systems plays a critical role in the aetiology and treatment of this disorder. Several case studies and open label trials have implemented bright light therapy (BT) in an attempt to repair sleep, depression and even the primary motor symptoms of this disorder, however controlled studies are yet to be fully implemented. In the present randomised, double blind, placebo controlled paradigm patients were exposed for 1 hour daily to either polychromatic light as the active treatment, red light or no light as controls for a 2 week period. The Movement Disorder Society- Unified Parkinson’s disease Rating Scale (MDSUPDRS), The Parkinson’s Disease Questionnaire (PDQ39), The Beck Depression Index II, The Beck Anxiety Index, The Epworth Sleep Scale (ESS) and a global rating scale were used to assess patients prior to and at 1 week and 2 weeks after commencing the trial. For patients continuing an established program of BT prior to study, significant improvement on the MDSUPDRS Rating Scale (12 points; p = 0.028), the PDQ-39 (10 points; p = 0.011), ESS (4 points; p = 0.013) and numerous motor and secondary symptoms on a global assessment were observed. Performance on standardised motor test also incrementally improved in this group while those exposed to red light and those without BT treatment deteriorated. These results demonstrate that strategically applied polychromatic light was beneficial in reducing many primary motor and secondary symptoms of PD. Further work investigating the role of light in mitigating PD symptoms and involvement of the circadian system will provide further advances in the treatment of PD.